The Cod's Tale - Kurlansky, Mark; Schindler, S. D. (CORE Scholar, 2001)
Describes the Atlantic cod fish and how it has been fished throughout history to near extinction. https://corescholar.libraries.wright.edu/dlpp_all/1059/thumbnail.jpg